ENTREPRENEURIAL COMPETENCIES DEVELOPMENT MODEL ON SMALL MEDIUM TOURISM ENTERPRISES (SMTEs) - Utami, Hamidah Nayati (Profit: Jurnal Adminsitrasi Bisnis, 2020)
The focus of this research is directed at identifying entrepreneurial competence of SMEs in the tourism sector, identifying competency development problems and formulating competency development models of SMTE players in supporting the realization of a sustainable tourism industry. The study was conducted in the National Tourism Strategic Area (KSPN) Bromo Tengger Semeru, East Java, Indonesia. The research method uses a qualitative approach with descriptive analysis techniques, data collection is done by in-depth interviews with the Regional Apparatus Organization and tourism sector SMEs. The results of this study indicate that: the level of entrepreneurial competence, namely knowledge, skills and entrepreneurial attitudes of the tourism sector SMEs is still relatively low; One of the factors that influence the low competency is the less optimal role of the government in increasing entrepreneurial competence, the pattern of coordination between regional organizations has not gone well and all stakeholders have not been involved in developing. Therefore, the proposed model for developing SMTE's entrepreneurial competencies is a collaborative governance approach on an ongoing basis.